The TECHNICAL AND ECONOMIC STUDY OF GAS REPLACEMENT WITH HYDROGEN IN CO-FIRING AT COMBINED CYCLE GAS TURBINE PLANT X - Setiawan, Mochamad Ryan; Saputera, Wibawa Hendra (ITB Graduate School Conference, 2025)
In supporting the transition to clean energy and achieving Net Zero Emission by 2060, the Indonesian government focuses on the power generation sector. Hydrogen co-firing, as a carbon-free fuel with high energy, is considered a potential solution to reduce carbon emissions and fuel costs. This study evaluates the technical, economic, and environmental aspects of implementing hydrogen co-firing technology at PLTGU Priok. The technical evaluation is conducted through modeling and simulation of the combustion process using Aspen Hysys, focusing on combustion efficiency and thermal conditions (TIT and TAT). The economic analysis includes determining the electricity tariffs per kWh after retrofitting and the Levelized Cost of Electricity (LCoE). According to the findings, 20% hydrogen cofiring was applied, meeting the TIT and TAT limits at 1350 and 600 degrees Celsius, respectively. The results can reduce CO2 emissions by 38.88% and increase combustion efficiency by 0.44%, with an LCOE value of IDR 1503.10/kWh. Emissions reduction and efficiency improvement assist national energy intuition targets over the long term, notwithstanding the significant initial investment required. This study provides guidance for policy makers in the development of hydrogen co-firing technology in Indonesia.